Infused Social Emotional Learning (SEL) Skills in Oral Communication Tasks - Yin, Xiaoyu; Ordonio, Mary Rose Mangonon (Journal of Education, Language Innovation, and Applied Linguistics, 2024)
This study aimed to identify the social-emotional learning skills infused in the oral communication tasks utilized in a Chinese Senior High school in Baguio City, Philippines. Through the use of qualitative descriptive research design and the rigorous process of document analysis, the researcher found out that the activities, tasks, and the whole curriculum in oral communication of the selected locale of the study highlight responsible decision-making to be the most evident hence prioritized SEL skill being developed in the said subject followed by relationship skills, social awareness, self-management, and self-awareness respectively based on the frequency of occurrences of these in said activities. Thus, it can be agreed based on the result that responsible decision-making has been focused predominantly on the activities used to develop skills concerning problem-solving and analyzing which are essential for students to be competitive in the 21st century. It can also be deducted that the curriculum of the said locale of the study should further include other SEL skills primarily highlighting social awareness and relationship skills, as they were perceived to be essential in oral communication. Keywords: Social-Emotional Learning (SEL); responsible decision-making; oral communication; social awareness; relationship skills.